2018
DOI: 10.18203/2349-2902.isj20185458
|View full text |Cite
|
Sign up to set email alerts
|

Iliopsoas abscess: clinical presentation, management, and outcome

Abstract: Background: The aim of this study was to review our experience with iliopsoas abscesses (IPAs) and evaluate the various drainage procedures.Methods: All consecutive patients with an IPA admitted to three university hospitals between September 2008 and June 2017 were retrospectively included.Results: Of the 26 patients, 17 (65.4%) were male and nine (34.6%) were female, with an average age of 30.7 (17-58) years. Fifteen (57.7%) cases had primary IPAs and Staphylococcus spp. was the most common isolate. Eleven (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 17 publications
5
10
1
Order By: Relevance
“…S. aureus was the most common causative bacterium with a higher complication rate of septic shock than other bacteria. The hospital mortality rate was 12%, which was similar to a previous report [ 1 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…S. aureus was the most common causative bacterium with a higher complication rate of septic shock than other bacteria. The hospital mortality rate was 12%, which was similar to a previous report [ 1 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown differences in clinical characteristics, treatments, and outcomes between patients with primary and secondary PA [ 2 , 16 , 17 ] as well as between patients with staphylococcal infection and other infections [ 1 , 2 , 18 ]. Therefore, we compared patients with primary and secondary PA and those with staphylococcal infection and other infections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the volume of abscess drained in Group B was larger in the present study, it was not statistically significant. There are studies reporting that the drainage time ranged from 2.4 to 45 days in psoas abscesses (18,27). No association was detected in our study between prolonged drainage time and recurrence.…”
Section: Discussioncontrasting
confidence: 66%
“…Clinical management with PCD and appropriate antibiotic therapy was safe and effective with shorter hospital stay for IPA. Open surgical intervention might be warranted if there was an underlying pathology [911]. Risk factors associated with mortality in IPA caused by CVD were found in our present study to include hypoalbuminemia, hyponatremia, involving disc/vertebral body and/or epidural abscess, and ICU stay with intubation > 3 days.…”
Section: Discussionmentioning
confidence: 50%